Increased incidence of bowel cancer after non-surgical treatment of appendicitis. Issue 11 (November 2017) - Enblad, Malin; Birgisson, Helgi; Ekbom, Anders; Sandin, Fredrik; Graf, Wilhelm
Abstract: Background: There is an ongoing debate on the use of antibiotics instead of appendectomy for treating appendicitis but diagnostic difficulties and longstanding inflammation might lead to increased incidence of bowel cancer in these patients. The aim of this population-based study was to investigate the incidence of bowel cancer after non-surgical treatment of appendicitis. Patients and methods: Patients diagnosed with appendicitis but lacking the surgical procedure code for appendix removal were retrieved from the Swedish National Inpatient Register 1987–2013. The cohort was matched with the Swedish Cancer Registry and the standardised incidence ratios (SIR) with 95% confidence interval (95% CI) for appendiceal, colorectal and small bowel cancers were calculated. Results: Of 13 595 patients with non-surgical treatment of appendicitis, 352 (2.6%) were diagnosed with appendiceal, colorectal or small bowel cancer (SIR 4.1, 95% CI 3.7–4.6). The largest incidence increase was found for appendiceal (SIR 35, 95% CI 26–46) and right-sided colon cancer (SIR 7.5, 95% CI 6.6–8.6). SIR was still elevated when excluding patients with less than 12 months since appendicitis and the incidence of right-sided colon cancer was elevated five years after appendicitis (SIR 3.5, 95% CI 2.1–5.4). An increased incidence of bowel cancer was found after appendicitis with abscess (SIR 4.6, 95% CI 4.0–5.2), and without abscess (SIR 3.5, 95% CI 2.9–4.1). Conclusion: Patients with non-surgical treatment of appendicitis have an increased short and long-term incidence of bowel cancer. This should be considered in the discussion about optimal management of patients with appendicitis.